Religion and Political Tolerance in America : Advances in the State of the Art - Djupe, Paul A. (Book collections on Project MUSE., 2015)
"Religious institutions are often engaged in influencing the beliefs and values that individuals hold. But religious groups can also challenge how people think about democracy, including the extension of equal rights and liberties regardless of viewpoint, or what is commonly called political tolerance. The essays in Religion and Political Tolerance in America seek to understand how these elements interrelate. The editor and contributors to this important volume present new and innovative research that wrestles with the fundamental question of the place of religion in democratic society. They address topics ranging from religious contributions to social identity to the political tolerance that religious elites (clergy) hold and advocate to others, and how religion shapes responses to intolerance. The conclusion, by Ted Jelen, emphasizes that religion's take on political tolerance is nuanced and that they are not incompatible; religion can sometimes enhance the tolerance of ordinary citizens"--